2005
DOI: 10.1111/j.1444-2906.2005.01011.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the quality and storage stability of fish burgers during frozen storage

Abstract: In an attempt to initiate seafood biotechnology in the Sultanate of Oman, Middle East, using underutilized fish, fish burgers from two different formulas were developed and the quality and storage stability were evaluated during storage at -20∞C for 3 months. Quality and storage stability were evaluated through total aerobic and coliform bacterial count, peroxide value, protein solubility, and color. Total aerobic bacteria were reduced significantly (P < 0.05) by 84% and 97% of the initial load in formulas 1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 21 publications
8
36
1
1
Order By: Relevance
“…All sample groups were softer and less rubbery after 6 months of frozen storage possibly due lipid oxidation and protein degradation during storage (Undeland and Lingnert, 1999;Ninan et al, 2008). Similar results were reported for fish finger (Tokur et al, 2006), fish burger (Al Bulushi et al, 2005), fish sausage (AlBulushi et al, 2013), fish cutlets (Talab, 2014) and fish ball (Shaviklo et al, 2010).…”
Section: Sensory Evaluationsupporting
confidence: 75%
See 1 more Smart Citation
“…All sample groups were softer and less rubbery after 6 months of frozen storage possibly due lipid oxidation and protein degradation during storage (Undeland and Lingnert, 1999;Ninan et al, 2008). Similar results were reported for fish finger (Tokur et al, 2006), fish burger (Al Bulushi et al, 2005), fish sausage (AlBulushi et al, 2013), fish cutlets (Talab, 2014) and fish ball (Shaviklo et al, 2010).…”
Section: Sensory Evaluationsupporting
confidence: 75%
“…However, it can be covered as mentioned before. Sensory quality of ready-to-eat fish products during frozen storage is dramatically influenced by chemical and microbial deterioration (Tokur et al, 2004;Calci et al, 2005;Al-Bulushi et al, 2005;Boran and Kose, 2007). Several techniques are used for preserving fishery formulated products.…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…While there was non-significant change during storage period in total coliform bacteria count in salmon döner samples stored at 4℃, significant decrease in the number of total coliform bacteria were detected in samples stored at −18℃ (P < 0.05). Similarly, Al-Bulushi et al (2005) reported significant reduction of coliform bacteria in fish burgers during storage at −20℃. On the other hand, molds and yeasts (2.70 log 10 cfu/g) were eliminated with heat treatment in döner kebab production (P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, fish and seafoods consumption are highly recommended to consumer as a means of improving health due to their PUFA composition. In this regard, possible usage of various fish species in manufacture of sausage (Berik and Kahraman, 2010), pastırma (Arslan and Kök, 2001), frankfurter (Sını et al, 2008), burger (Al-Bulushi et al, 2005;Metin, 2002) and köfte (Öksüztepe et al, 2010) have been investigated. However, there is a lack of information in literature about possible usage of fish in manufacture of döner kebab which is one of the most consumed fast food product in the world.…”
Section: Introductionmentioning
confidence: 99%
“…However, after day 6 of storage, the SEP content in garlic treated (T4 andT3) samples were significantly (P < 0.05) higher than in the C, T1 and T2 samples. From the SEP results, noted that addition of ginger in a samples resulted to largest SEP loss throughout the storage time, compared to control samples, this result indicated that the higher protein denaturation and damage associated with the proteolytic activity of ginger incorporated [2,20].The antioxidant efficiency of garlic is due to rich in organsulfur compounds and their precursors (allicin, diallyl sulfide and diallyl trisulfide) have biological actions to retard lipid oxidation [14,22,37], resulted to lowest SEP loss throughout the storage time for garlic incorporated samples, compared to control and ginger treated samples, since interaction between protein and lipid oxidation products, causing a decline of protein solubility [3,34]. The decrease in SEP for control samples during frozen storage could be resulted from the formation of hydrogen or hydrophobic bonds, as well as disulfide bonds and ionic interactions [5,32,36].…”
Section: Salt Extractable Proteinmentioning
confidence: 99%